EXPERIENCE IN IMPLEMENTING ELECTRONIC CRIMINAL PROCEEDINGS IN SOME FOREIGN COUNTRIES - Rakhimova, Ulzana (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article explores the experiences of various countries in implementing electronic criminal case management systems, highlighting both the advantages and challenges encountered. In the United States, the adoption of systems like PACER and CM/ECF has modernized the judicial process, though concerns about security and technical difficulties persist. Japan's introduction of electronic criminal proceedings in 2009 led to significant improvements in efficiency but also faced technological and security challenges. The UK, Canada, and Singapore have also implemented similar systems, each achieving varying degrees of success in enhancing the efficiency and accessibility of their criminal justice systems. The article concludes that while electronic case management systems offer significant benefits, careful consideration must be given to their design and implementation to address potential risks and ensure their effectiveness..